Effective Strategies in Human Resource Management to Improve Productivity - Anastasya Putri Yudiana (Digital Innovation : International Journal of Management, 2025)
Effective human resource (HRM) management is a key factor in improving organizational productivity. This research discusses strategies that can be implemented in human resource management, such as competency-based recruitment, continuous training and development, a transparent performance evaluation system, as well as welfare policies and a fair reward system. Implementing this strategy not only contributes to improving individual and team performance, but also creates a positive work environment, increases employee motivation and satisfaction, and optimizes operational efficiency through the use of technology. In facing global challenges such as digitalization and labor competition, companies must adapt their HR strategies to emerging trends, including workforce diversification and the creation of an inclusive organizational culture. By implementing an HR strategy that is in line with the company’s vision and mission, organizations can optimally utilize employee potential, increase competitiveness, and achieve higher productivity in the era of globalization